AN ANALYSIS OF STUDENTS’ LEARNING STYLE IN SPEAKING SKILL AT SMAN 1 TEMBILAHAN HULU - Muhammad Faishal Amin; Melda Yeni; Maizarah; Destri Wahyuningsih (J-Shelves of Indragiri (JSI), 2026)
Learning style is an important factor in the process of language acquisition, especially in speaking skills that require understanding and confidence. This study examines the dominant learning styles of grade XI students of SMAN 1 Tembilahan Hulu in learning to speak English. With a quantitative descriptive approach and an instrument in the form of a questionnaire, data were obtained from 100 respondents. The results of the analysis showed that auditory learning style is the most dominant learning style, with the highest average score (296), compared to visual and kinesthetic learning styles. This shows that students find it easier to develop their speaking skills through listening activities and imitating pronunciation. These findings are the basis for teachers and educational institutions to adjust teaching methods to align with students' learning styles.